The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10508-014-0375-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Youth Homelessness, Sexual Offenses, Sexual Victimization, and Sexual Risk Behaviors: A Systematic Literature Review

Abstract: Homeless youth commonly report engaging in sexual risk behaviors. These vulnerable young people also frequently report being sexually victimized. This systematic review collates, summarizes, and appraises published studies of youth investigating relationships between homelessness, perpetration of sexual offenses, experience of sexual victimization, and engagement in sexual risk behavior. A systematic search of seventeen psychology, health, and social science electronic databases was conducted. Search terms inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 73 publications
0
55
0
4
Order By: Relevance
“…Other research has focused on exchange of sex (also defined in the literature as trading sex or survival sex) has primarily targeted homeless and runaway adolescents and young adults [13, 14, 18, 20, 23, 25, 26] and varying correlates identified in these populations. A number of the studies found that exchange of sex varied by sexuality with little variation identified by gender.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has focused on exchange of sex (also defined in the literature as trading sex or survival sex) has primarily targeted homeless and runaway adolescents and young adults [13, 14, 18, 20, 23, 25, 26] and varying correlates identified in these populations. A number of the studies found that exchange of sex varied by sexuality with little variation identified by gender.…”
Section: Introductionmentioning
confidence: 99%
“…Another study focused on homeless male adolescents indicate that 15 % identified as gay [14], and Marshall et al [20] reported that 13.4 % of the street-involved youth in their study were ‘sexual minorities’. Other correlates of exchange of sex among homeless and runaway adolescents and young adults, include histories of physical and sexual abuse, drug use, and family dysfunction [13, 19, 23, 26, 27]; other findings have identified mental health (e.g., suicide attempts, depression), sharing needles for substance use, and prior history of HIV testing as correlates of exchange of sex in homeless youth [13, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that disadvantage, particularly life on the streets, is associated with youth engaging in more risky behavior (e.g. Gruber 2009;Cobb-Clark et al 2012;Omura et al 2014;Heerde et al 2015), which may increase contact with police. Not surprisingly, the homeless are dramatically over-represented in the prison population (Greenberg and Rosenheck 2008).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…While some find that sexual victimization is associated with running away earlier, others find the opposite. See Heerde et al (2015) for a review.…”
Section: The Mediating Effects Education Incarceration and Welfare Usementioning
confidence: 99%
“…Özellikle, cinsel davranışlar (Gonzalez-Blanks ve Yates, 2016;Heerde, Scholes-Balog ve Hemphill, 2015;Lalor ve McElvaney, 2010), intihar (Devries vd., 2014;Soylu ve Alpaslan, 2013), evden kaçma (Heerde vd., 2015), sigara kullanımı (Sartor vd., 2013), alkol ve madde kullanımı (Bergen, Martin, Richardson, Allison ve Roeger, 2004;Gidycz vd., 1995;Sartor vd., 2013) Cİ için risk faktörleri olarak değerlendirilmektedir. Gonzalez-Blanks ve Yates (2016) cinsel istismarın ve devlet yurdunda yaşamanın ergenlerin cinsel riskli davranışlar sergilemeleri ile ilişkili olduğunu ve ergenlerin dissosiyatif belirtilerinin cinsel istismar ve riskli davranışlar arasındaki ilişkiyi güçlendirdiğini belirlemişlerdir.…”
Section: Introductionunclassified